Pengaruh Bauran Pemasaran Jasa Dan Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Muhammadiyah Sumatera Utara - Dedek Kurniawan Gultom; Paham Ginting; Beby KF Sembiring (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The objective of the research was to find out and to analyze to what extent the influence of service marketing mix and service quality on students’ satisfaction in Management Study Program, Faculty of Economics, UMSU. The type of the research was an explanatory study. The result of the research showed that service marketing mix which consisted of product, location, process, people, physical evidence, and service quality which consisted of direct evidence, reliability, response, security, and empathy simultaneously had positive influence on students’ satisfaction, while the cost for education had negative influence.